2021
DOI: 10.1007/s00259-021-05611-w
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution pediatric age–specific 18F-FDG PET template: a pilot study in epileptogenic focus localization

Abstract: Background PET imaging has been widely used in diagnosis of neurological disorders; however, its application to pediatric population is limited due to lacking pediatric age–specific PET template. This study aims to develop a pediatric age–specific PET template (PAPT) and conduct a pilot study of epileptogenic focus localization in pediatric epilepsy. Methods We recruited 130 pediatric patients with epilepsy and 102 age-matched controls who underwent 18F-FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Most neuroimaging studies concentrated on cognitive impairments of language, attention, and working memory in ECTS patients [ 1 , 3 ]; however, only one study investigated processing speed [ 21 ]. Our study, together with the previous study, showed that processing speed could be impaired in patients with ECTS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most neuroimaging studies concentrated on cognitive impairments of language, attention, and working memory in ECTS patients [ 1 , 3 ]; however, only one study investigated processing speed [ 21 ]. Our study, together with the previous study, showed that processing speed could be impaired in patients with ECTS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET images were preprocessed by Statistical Parametric Mapping (SPM8; https://www.fil.ion.ucl.ac.uk/spm ), FSL ( https://fsl.fmrib.ox.ac.uk/fsl/fslwiki ) [ 19 ], and FreeSurfer ( https://surfer.nmr.mgh.harvard.edu/ ) [ 20 ]. All 18 F-FDG PET images of ECTS patients and controls were spatially normalized to an in-house pediatric 18 F-FDG PET template, followed by Gaussian smoothing with 6-mm full-width half-maximum (FWHM) [ 21 ]. Standardized uptake value ratio (SUVR) was determined to normalize intensities by using cerebellum gray matter as the reference region [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional deficit zone in pediatric epilepsy using in-house age-specific FDG-PET templates by linear registration between PET images and pediatric MRI template showed better agreement with the clinical diagnosis than using the in-built adult control dataset (99). A pediatric-age-specific FDG-PET template based on a nonlinear optimization method improved spatial normalization and showed better EZ localization than using the adult template and linear template (100). Three-dimensional stereotactic surface projection (3D-SSP; NEUROSTAT) software is another user-friendly voxel-based brain mapping software for FDG-PET, which was proven to improve EZ detection compared with visual assessment and MRI and its performance is comparable with SPM analysis (101).…”
Section: Brain Fdg-petmentioning
confidence: 99%
“…
18 F]fluorodeoxyglucose (FDG) positron emission tomography (PET) has emerged as a crucial tool in identifying the epileptic focus, especially in cases where magnetic resonance imaging (MRI) diagnosis yields indeterminate results. FDG PET can provide the metabolic information of glucose and help identify abnormal areas that are not easily found through MRI.
…”
mentioning
confidence: 99%